Social policy as a factor in employment regulation in the labor market of Russia - K. A. Prozorovsky (Путеводитель предпринимателя, 2023)
The article considers the problems of forming an optimal social policy that would allow building a more effective employment policy in the Russian labor market. The social policy of the state should ensure social stability, contribute to the equalization of the incomes of the population in the sectoral and regional sections, but not generate a class of dependents who can exist exclusively on state benefits.The author considers the structure of employment of the population, which determines the existing contradictions in the tax, pension and social systems. The paper analyzes the problems of the Russian labor market that have developed over many years of the market economy.The author notes the social orientation of the state in its budget policy, the share of social expenditures is growing, but in many respects they are tactical in nature.There is a need to revise the current social policy in the country on the basis of reforming the taxation system.